Power Imbalance Analysis of Modular Multilevel Converter With Distributed Energy Systems - Tomas Salvadores; Javier Pereda; Felix Rojas (IEEE Open Journal of the Industrial Electronics Society)
The modular multilevel converter (MMC) can integrate distributed energy systems (DES), such as a battery energy storage system, to expand its functionalities and carry out multiple simultaneous tasks. However, a DES induces power imbalances within the MMC, which affects the operating currents and voltages of the converter. This phenomenon has been partially covered in recent works, but an analytical analysis has not yet been carried out to see the behavior and implications in different MMC-DES applications. This article introduces a novel analytical analysis of the power imbalances between MMC clusters. It pioneers the development of general equations and imbalance capability metrics, enabling the assessment of maximum currents and voltages supported by the MMC clusters. The developed tools allow the evaluation of any MMC-DES application regarding the current and voltage rating requirements of MMC clusters. The analysis shows that the MMC operating mode can substantially restrain or enlarge its imbalance capacity, affecting its suitability for different DES applications. While it needs around 33% current overrating in the worst imbalances, under some operating modes it can reach most imbalances without requiring current overrating. The ac compensation mode is much more capable of achieving imbalances than the dc compensation mode, reaching 88.37% and 16.74% of the imbalance points, respectively, without requiring any overrating.